Metabolic remodeling in takotsubo syndrome - Ti Wang; Ting Xiong; Yuxue Yang; Bangyun Zuo; Xiwei Chen; Daxin Wang (Frontiers in Cardiovascular Medicine, 2022)
The heart requires a large and constant supply of energy that is mainly the result of an efficient metabolic machinery that converges on mitochondrial oxidative metabolism to maintain its continuous mechanical work. Perturbations in these metabolic processes may therefore affect energy generation and contractile function directly. Metabolism characteristics in takotsubo syndrome (TTS) reveals several metabolic alterations called metabolic remodeling, including the hyperactivity of sympathetic metabolism, derangements of substrate utilization, effector subcellular dysfunction and systemic metabolic disorders, ultimately contributing to the progression of the disease and the development of a persistent and long-term heart failure (HF) phenotype. In this review, we explore the current literature investigating the pathological metabolic alterations in TTS. Although the metabolic dysfunction in takotsubo hearts is initially recognized as a myocardial metabolic inflexibility, we suggest that the widespread alterations of systemic metabolism with complex interplay between the heart and peripheral tissues rather than just cardiometabolic disorders per se account for long-term maladaptive metabolic, functional and structural impairment under this condition. Therapeutic strategies with the recent evidence from small clinical and animal researches, especially for targeting substrate utilization and/or oxidative stress, might be promising tools to improve the outcome of patients with TTS beyond that achieved with traditional sympathetic inhibition and symptomatic therapies.